Discerning Reported Suicide Attempts Within a Youthful Offender Population - Dare, Paricia Stoddard (2012)
With suicide being the third leading cause of death among young people, early identification of risk is critical, particularly for those involved with the juvenile courts. In this study of court-involved youth (N = 433) in two Midwest counties, logistic regression analysis identified some expected and unexpected findings of important demographic, educational, mental health, child welfare, and juvenile court-related variables that were linked to reported suicide attempts. Some of the expected suicide attempt risk factors for these youth included prior psychiatric hospitalization and related mental health services, residential placement, and diagnoses of depression and alcohol dependence. However, the most unexpected finding was that a court disposition to shelter care (group home) was related to a nearly tenfold increased risk in reported suicide attempt. These findings are of importance to families, mental health professionals, and juvenile court personnel to identify those youth who are most at risk and subsequently provide appropriate interventions to prevent such outcomes